2018
DOI: 10.2174/1381612823666170817125015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Excitotoxic Lesion with Inhaled Anesthetics on Nervous System Cells of Rodents

Abstract: Different anesthesia methods can variably influence excitotoxic lesion effects on the brain. The main purpose of this review is to identify potential differences in the toxicity to nervous system cells of two common inhalation anesthesia methods, isoflurane and sevoflurane, used in combination with an excitotoxic lesion procedure in rodents. The use of bioassays in animal models has provided the opportunity to examine the role of specific molecules and cellular interactions that underlie important aspects of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 116 publications
(136 reference statements)
0
5
0
Order By: Relevance
“…Apoptosis has been shown to be no longer demonstrable as early as 48h after exposure to dizocilpine 21 . Dizocilpine is a noncompetitive NMDA antagonist 47 , which is presumed to impact the fetal brain through a similar mechanism as sevoflurane 48 . The presence of in utero deceased fetuses, which is not uncommon in rabbits, may also have an effect on neurodevelopment, e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Apoptosis has been shown to be no longer demonstrable as early as 48h after exposure to dizocilpine 21 . Dizocilpine is a noncompetitive NMDA antagonist 47 , which is presumed to impact the fetal brain through a similar mechanism as sevoflurane 48 . The presence of in utero deceased fetuses, which is not uncommon in rabbits, may also have an effect on neurodevelopment, e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It suggests that anesthetics may alter the function of microglia. Inhaled anesthetics have been demonstrated to cause neuroinflammation by activating microglia and may be involved in PND (Shen et al, 2013;Yan et al, 2016;Quiroz-Padilla et al, 2018;Wang et al, 2018). But a recent study showed that exposure to sevoflurane anesthesia for 8 h did not alter microglial activation in the adult monkey.…”
Section: General Anestheticsmentioning
confidence: 96%
“…However, the exact mechanism by which sevoflurane damages the central nervous system (CNS) is not fully understood. So far, sevoflurane may damage the CNS through the following mechanisms: neuronal apoptosis (Bi et al, 2018; Wang & Zhou, 2018), endoplasmic reticulum stress, neuroinflammation (Wang et al, 2014; Wang et al., 2019), oxidative stress‐induced reactive oxygen species (ROS) accumulation (Xu & Qian, 2020; Zhou, 2018), neurotransmitter disturbances (Moore & Anghelescu, 2017), autophagy (Li et al, 2017; Zhang et al, 2016), necrosis (Quiroz‐Padilla et al., 2018), and changes in synaptic plasticity (Xiao et al., 2016). These mechanisms are too closely related to each other to function independently (Song et al, 2018).…”
Section: Sevoflurane Neuroapoptosis and Neuroinflammationmentioning
confidence: 99%